Perlindungan Konsumen di Masa Pandemi Covid-19 Sebagai Wujud Pemenuhan HAM - Celina Tri Siwi K (Faculty of Law, Universitas Airlangga, 2022)
AbstractThe negative effects of the COVID-19 pandemic are bringing problems to the protection of consumer rights. This happens when their access to basic goods and services is already poor due to unfair economic practices, unhealthy business competition. Consumer rights are regulated in Law No. 8 of 1999 concerning Consumer Protection Article 4. Pandemic times with various impacts caused along with the era of disruption, causing consumers to be in a weak position. This falls into the category of social context influenced by access to technology or the context of the economic power of a society. The handling of the COVID-19 pandemic, or other emergencies, is not only determined and regulated by national legislation or legislation, but also by international human rights law, especially those that have been ratified or officially recognized by the country concerned. For example, in the context of dealing with a pandemic or other health crisis, The International Covenant on Economic, Social and Cultural Rights (ICESCR) – under which Indonesia has ratified it through Law No. 12 of 2005 – states that